2022
DOI: 10.1108/ecam-02-2022-0111
|View full text |Cite
|
Sign up to set email alerts
|

How are social procurement actors shaping a new field of professional practice in the Australian construction industry?

Abstract: PurposeSocial procurement is becoming an increasing policy focus for governments around the world as they seek to incentivise new collaborative partnerships with private organisations in industries like construction to meet their social obligations. The limited construction management research in this area shows that the successful implementation of these policies depends on a new generation of social procurement professionals who are promoting these policies into an institutional vacuum with little organisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…There have been calls for the development of training and educational courses for all stakeholders about the need to shift to sustainable procurement practices (e.g., [39,49,72]) and for the development of the skills and competencies needed to implement social procurement [11,29]. This is a clear need.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been calls for the development of training and educational courses for all stakeholders about the need to shift to sustainable procurement practices (e.g., [39,49,72]) and for the development of the skills and competencies needed to implement social procurement [11,29]. This is a clear need.…”
Section: Discussionmentioning
confidence: 99%
“…Adopt a more person-centric approach to the design and implementation of solutions and a more holistic approach to the measurement of impacts and outcomes. Understand the project context and ensure bespoke solutions rather than use a standardised tool measured against project management metrics and targets-Murphy, and Eadie [51] Support on the change -Appoint more than one social value champion to implement social procurement who each plays a multitude of roles at different organisational levels and across different organisational functions-Loosemore, Keast, and Barraket [39]…”
Section: Generalmentioning
confidence: 99%
“…The co-authorship network visualization was ignored since there was a link between just two countries under analysis which is Australia and the United Kingdom, unlike other studies that showed the network [4]. Loosemore and co-authors can be seen to be leading research in SV literature in the construction sector [25,26,28,29,[43][44][45][46]. It is also noteworthy that many of these leading authors of SV in the construction industry are affiliated with universities in Australia.…”
Section: Analysis Of Co-authorship and Publication Per Authormentioning
confidence: 99%
“…The co-authorship network visualization was ignored since there was a link between just two countries under analysis which were Australia and the United Kingdom, unlike other studies that showed a larger network [4]. Loosemore and co-authors can be seen to be leading the research on SV in the construction sector [25,26,28,29,[64][65][66][67]. It is also noteworthy that many of these leading authors on SV in the construction industry are affiliated with universities in Australia.…”
Section: Analysis Of Co-authorship and Publications Per Authormentioning
confidence: 99%